2014
DOI: 10.1007/s11999-014-3747-y
|View full text |Cite
|
Sign up to set email alerts
|

How is Forearm Compliance Affected by Various Circumferential Dressings?

Abstract: Background The forearm is the second most common location for extremity compartment syndrome. Compliance is a physical property that describes a material's ability to expand with an increasing internal volume. The effect of circumferential dressings on extremity pressures has been investigated in various animal models and in some nonphysiologic mechanical models, but the importance of this effect has not been fully investigated in the human upper extremity. In addition, the physical property of compliance has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Many studies have evaluated the below-dressing pressure changes that occur when a cast and/or its underlying padding is split, with uniform demonstration of significant reduction in pressures with increased layers being released. [2][3][4][5][6][7][8][9] These authors have also demonstrated that overwrapping a cast with an elastic bandage after splitting the cast results in a decreased overall pressure reduction and therefore the wrap should be applied gently or not at all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have evaluated the below-dressing pressure changes that occur when a cast and/or its underlying padding is split, with uniform demonstration of significant reduction in pressures with increased layers being released. [2][3][4][5][6][7][8][9] These authors have also demonstrated that overwrapping a cast with an elastic bandage after splitting the cast results in a decreased overall pressure reduction and therefore the wrap should be applied gently or not at all.…”
Section: Discussionmentioning
confidence: 99%
“…Splitting a cast, splint, or the underlying padding can significantly decrease pressure on the extremity. [2][3][4][5][6][7][8][9] The tension with which an elastic bandage is applied over a splint can significantly affect the pressure on the underlying forearm. 2 Many surgeons have advocated for the use of a bias cut stockinette instead of an elastic bandage (commonly referred by the brand name "ACE" wrap) to reduce the risk of pressure-related complications.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have identified that fiberglass casts are the least compliant dressing, followed by sugar tong splints and elastic wraps. 9 However, no study to date has studied the compliance of split dressings. Our study reaffirms the notion that swelling can dramatically increase below-dressing pressure, particularly under a cast.…”
Section: Discussionmentioning
confidence: 99%
“…Die Verwendung einer intrakompartimentellen Druckmessung hierfür ist umstritten, sollte aber bei Patienten Anwendung finden, die zum Beispiel nach einem Polytrauma nicht adäquat klinisch untersucht werden können (Mcqueen et al 2013). Zirkuläre Verbände sollten bei einem klinischen Verdacht umgehend eröffnet werden (Capo et al 2014). Besteht nach einer Fraktur im Rahmen der operativen Versorgung der Verdacht auf ein Kompartmentsyndrom, sollte bereits primär eine Dermotraktion angelegt und die Wunde erst sekundär verschlossen werden.…”
Section: Kompartmentsyndromunclassified